2013
DOI: 10.6090/jarq.47.283
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Zingiberaceae Plant Isolates of Ralstonia solanacearum in the Asia-Pacific Region

Abstract: The genetic diversity of Ralstonia solanacearum strains isolated from Zingiberaceae plants in the Asia-Pacific region was assessed by examining their biochemical properties, discriminating the phylogeny by polymerase chain reaction (PCR), and analyzing the egl and mutS gene sequences. These data were compared with those of reference strains covering the known diversity within the R. solanacearum species complex. Fifty-two of the Zingiberaceae plant isolates belong to either biovar 3 or biovar 4. Multiplex PCR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Since 2005, the pathogen has been spreading to ginger fields in prefectures outside Kochi such as Tochigi (Waki et al 2013). Biovar classification of the isolates from Kochi Prefecture revealed that all of the strains were identical to biovar 4; however, the ginger strains from Tochigi Prefecture belonged to biovars 3 and 4 (Waki et al 2013). …”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Since 2005, the pathogen has been spreading to ginger fields in prefectures outside Kochi such as Tochigi (Waki et al 2013). Biovar classification of the isolates from Kochi Prefecture revealed that all of the strains were identical to biovar 4; however, the ginger strains from Tochigi Prefecture belonged to biovars 3 and 4 (Waki et al 2013). …”
Section: Introductionmentioning
confidence: 95%
“…On the other hand, Japanese strains can be divided into 2 phylotypes (I and IV) and 11 sequevars, and phylotypes I and IV consist of 9 and 2 sequevars, respectively Waki et al 2013). Strains in phylotype II or III have not been isolated so far in the country.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In Japan, bacterial wilt of ginger family plants caused by R. solanacearum has been reported on ginger, mioga and siam tulip (curcuma) (Morita et al 1996;Tsuchiya et al 1999;Yano et al 2005), and all strains belonged to race 4, biovar 4 and phylotype I (Waki et al 2013). Japanese race 4 strains also have been subclassified into two DNA types (type I and II) based on repetitive sequence-based PCR (rep-PCR) DNA fingerprint analysis, and PCR primer sets for specific detection, and discrimination of each DNA type within race 4 strains has been reported (Horita et al 2004;Horita and Tsuchiya 2012).…”
mentioning
confidence: 97%